2011
DOI: 10.1017/s1368980011001352
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional knowledge in European adolescents: results from the HELENA (Healthy Lifestyle in Europe by Nutrition in Adolescence) study

Abstract: Objective: To build up sufficient knowledge of a 'healthy diet'. Here, we report on the assessment of nutritional knowledge using a uniform method in a large sample of adolescents across Europe. Design: A cross-sectional study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
67
4
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(89 citation statements)
references
References 41 publications
12
67
4
6
Order By: Relevance
“…Previous research on athletes [25–27] and nonathletes [28] had already shown important nutrition concerns. For instance, poor knowledge of the foods required for refueling, sport drinks, and the role of protein in muscle formation was found in Irish rugby players aged 15–18 yr [27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research on athletes [25–27] and nonathletes [28] had already shown important nutrition concerns. For instance, poor knowledge of the foods required for refueling, sport drinks, and the role of protein in muscle formation was found in Irish rugby players aged 15–18 yr [27].…”
Section: Discussionmentioning
confidence: 99%
“…In a research on female collegiate swimmers there was lack of knowledge of nutrition [25], whereas in a research on female collegiate cross-country runners it was suggested that these athletes lacked nutrition knowledge critical to preventing nutrition-related health problems [26]. A modest nutrition knowledge and misconception with respect to the sugar content in food or in beverages were recorded in a large sample of adolescents aged 12.5–17.5 yr [28]. Consequently, the findings of this study combined with those of previous research indicated the need for nutrition education of athletes.…”
Section: Discussionmentioning
confidence: 99%
“…A dichotomous variable was created to distinguish parents with a ‘native’ background (i.e., both parents were born in the country of administration) from those with a ‘non-native’ background (i.e., at least one parent was born in another country). Country of birth of parents has been used to assess ethnic background or immigrant status in other recent cross-European research [35]. …”
Section: Methodsmentioning
confidence: 99%
“…Nutritional knowledge and attitude have been shown to influence dietary practices and consequently the quantity and quality of nutrients derived from a given food item (Hoogenboom, Morris, Morris, & Schaefer, 2009; Sichert‐hellert et al., 2011). Factors associated with nutritional knowledge and attitude such as choice of food, prior knowledge of expected nutritional benefits, and the frequency of consumption have been shown to influence household food and nutrition security (Carrillo, Varela, & Fiszman, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Factors associated with nutritional knowledge and attitude such as choice of food, prior knowledge of expected nutritional benefits, and the frequency of consumption have been shown to influence household food and nutrition security (Carrillo, Varela, & Fiszman, 2012). Despite the well‐known significance of appropriate nutritional knowledge and attitude on food consumption behavior, it is important to appreciate that much of the understanding has been derived from studies conducted among affluent societies using commercial food products (Hoogenboom et al., 2009; Scully, Dixon, & Wakefield, 2008; Sichert‐hellert et al., 2011). However, there is very limited information on the status of nutritional knowledge and attitude associated with consumption of wild fruits and vegetables among rural households such as those in Acholi subregion of Uganda.…”
Section: Introductionmentioning
confidence: 99%